An Eco-benign Synthesis of AgNps using Hydroalcoholic Extract of Brassica oleracea var. italica Plenck : Anticancer Response against Human Breast Cancer Cells MCF-7 - Chintamani, Ravindra Bhausaheb; Salunkhe, Kishor S.; Kharat, Kiran R.; Chavan, Macchindra J. (Journal of Drug Delivery and Therapeutics, 2019)
Breast Cancer is the second foremost reason of Cancer mortality in females globally. The conventional treatments available for Breast Cancer include surgery yet they are related to serious side effects that have moved the worldwide focus towards Complementary and Alternative Medicines (CAM). One of the emerging strategies has been the use of plant extracts for synthesizing metal nanoparticles (such as gold and silver) for anticancer applications. The objective of this study is to reflect the current availed study on green synthesis of silver nanoparticles (AgNps) with its future prospects to treat Breast Cancer. The development of eco-friendly and reliable techniques for silver nanoparticles synthesis is a vital initiative in the area of nanotechnology. Brassica oleracea var. italica Plenck Leaves Extract (LE) prepared by maceration process and silver nanoparticles of LE prepared by using biological reduction method. Female rats were divided into 5 groups, Group-I served as Positive Control and received normal saline. Group-II served Negative Control (Tumor Bearing) and was treated with single dose of MCF 7. Breast Cancer Cells (1.7 mg/pellet). Group-III served Standard Control (Tumor Bearing) treated with Paclitaxel 40 mg/Kg. Group-IV served test and treated with LE 400 mg/Kg, Group-V served test and treated with LENP 400 mg/Kg respectively about 21 days and on 21th day blood samples were collected for Hematological Parameters and Feed and Water Consumption, Body Weight Determination and Organ Weight were estimated. These discoveries infer that the synthesized Silver nanoparticles utilizing green nanotechnology could be a perfect methodology to battle malignant growth and irresistible ailments.Keywords:  Breast Cancer, Nanotechnology, Synthesis, , MCF-7, CAM